The challenges of environmental protection in the Republic of North Macedonia - Lažetić Gordana; Mujoska-Trpevska Elena (Temida)
Dealing with climate change and environmental issues must begin with the acceptance of the position that the environmental crisis is equivalent to the economic, political, or health crisis, which is typically the focus of our political and legal apparatus. It has such a broad scope that it exceeds the level of the individual right to a healthy environment and cannot be measured solely through the lens of concretely determined cases of violation. Its visible consequences cannot be justified by achieving some higher economic, social, or other goals, such as, first and foremost, economic benefits from accelerated economic development at the expense of reckless environmental destruction. Numerous laws and regulations in the Republic of North Macedonia cover almost every aspect of the environment. However, some of them are considered outdated and unsuitable for the country’s current situation. Another perceived weakness of the environmental legal framework is the lack of implementation as a result of the institutional division of state authorities responsible for enforcement and insufficient personnel and technical resources in local administration and inspection services. It is encouraging that the entire environmental legislation is being revised and perceived flaws are being addressed. Despite the beginning of the process of enacting new or amending existing laws for specific areas of environmental protection, many open questions remain in key areas as well as strategic goals and policies. This paper begins with an overview of the most important international standards as well as an introduction to green victimology specifics. Then the level of developed environmental awareness in the Republic North Macedonia is assessed through statistical data analysis. The authors specifically mention ecocide as a separate offence in the Criminal Code, among other novelties. The last part of the article is dealing with dilemmas regarding judicial protection of the right to protection of the environment, using examples from Macedonian judicial practice, they discuss the difficulties in judicially protecting the right to a healthy environment.